Reconfigurations in the post-Soviet South: Dynamics and change in Eurasia - Andrea Schmitz; Franziska Smolnik (Stiftung Wissenschaft und Politik (SWP), 2024)
Russia's invasion of Ukraine has accelerated global dynamics that profoundly impact the post-Soviet South. Relations with Russia are still strong, but the former subalterns are raising their voices. The empowerment is most visible in their foreign relations, but also tends to strengthen incumbent regimes and the political structures on which their power is built. A widening radius of interaction reinforces perceptions of collective agency and reduces the incentives for political reform. The persistence of authoritarianism parallels the diminishing soft power of the EU and the West in general. In dealing with more assertive Eurasian partners the EU will have to come up with credible offers to strengthen existing relations and harmonise its policies for impact.
Keywords: 320; Central Asia; South Caucasus; Eurasia; Armenia; Azerbaijan; Georgia; Kazakhstan; Kyrgyzstan; Tajikistan; Ukraine; Uzbekistan; Near Abroad; Eurasian Economic Union; EEU; authoritarianism; Great Patriotic War; orthodox faith; Belt and Road Initiative; BRI; Organisation of Turkic States; OTS; Collective Security Treaty Organisation; CSTO; Ilham Aliyev; Shavkat Mirziyoyev; Kassym-Jomart Tokayev; 3+3 platform